A Wideband Controllable Bandpass Filter Based on Spoof Surface Plasmon Polaritons - Chen, Xi; Cheng, Chonghu; Liu, Leilei (Frontiers in Physics, 2022)
A wideband controllable band-pass filter is proposed, which is based on the spoof surface plasmon polaritons (SSPP) and slip ring resonators (SRR). The design concept of the bandpass filter is using the SSPP and SRR to control the high cut-off frequency and filter the low-frequency wave, respectively. The bandpass filter is used diode reconfigurable technology to tunable the bandwidth. The filter has a passband range of 5–9 GHz, an out-band rejection of −20 dB for the lower sideband, and an out-band rejection of −50 dB for the upper sideband. The simulated and measured results are in good agreement over the operating band. Benefit from its low-profile and low-cost, the proposed bandpass filter has a great potential for development in plasmonic functional devices at microwave frequencies.